Microstructure and electro-optical properties of sol-gel derived Cd-doped ZnO films - Yakuphanoğlu, Fahrettin; Ilican, Saliha; Caglar, Mujdat; Caglar, Yasemin (Academic Press Ltd- Elsevier Science Ltd, 2010)
The microstructure, and the electrical and optical properties of undoped zinc oxide (ZnO) and cadmium-doped ZnO (CZO) films deposited by a sol-gel method have been investigated. The films have a polycrystalline structure with hexagonal wurtzite ZnO. Scanning electron microscopy (SEM) images indicated that the films have a wrinkle network with uniform size distributions. The elemental analyses of the CZO films were carried out by energy dispersive X-ray analysis. The fundamental absorption edge changed with doping. The optical band gap of the films decreased with Cd dopant. The optical constants of the films such as refractive index, extinction coefficient and dielectric constants changed with Cd dopant. A two-probe method was used to investigate the electrical properties, and the effect of Cd content on the electrical properties was investigated. The electrical conductivity of the films was improved by incorporation of Cd in the ZnO film. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Cd-doped ZnO; Sol-gel; Microstructure; Optical constants; Shrinkage effect; Electrical conductivity